Experimental evidence for a shallow cumulate remelting origin of lunar high-titanium mare basalts - Shuchang Gao; Yanhao Lin; Wim van Westrenen (Communications Earth & Environment)
Abstract High-titanium mare basalts were among the earliest rocks to be returned from the Moon, but key aspects of their formation remain enigmatic. Here we show twenty partial remelting experiments conducted on three bulk compositions based on shallow ilmenite-bearing cumulate compositions from experimental studies of lunar magma ocean crystallization, with varying amounts of plagioclase. Melts produced at about 1200–1250 °C and 0.4 gigapascal with residual iron metal, representing approximately 40 percent partial melting, are close to high-Ti mare basalt compositions in terms of both TiO2 content and magnesium number. These results, compared with Monte-Carlo simulations and modelled rare earth element abundances and samarium–neodymium-lutetium–hafnium isotopic signatures of the experimental melts, remove the requirement of a deep origin of the lunar high-Ti mare basalts. Instead, they provide new evidence supporting the hypothesis that high-degree impact-induced partial melting at shallow depth, with minor post-formation modification, played a key role.